2014
DOI: 10.1242/dev.095323
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that Nkx2.2 and Pdgfra are major determinants of the timing of oligodendrocyte differentiation in the developing CNS

Abstract: In the central nervous system (CNS), oligodendrocyte maturation and axonal myelination occur on a predictable schedule, but the underlying timing mechanisms are largely unknown. In the present study, we demonstrate that Nkx2.2 homeodomain transcription factor is a key regulator for the timing of oligodendrocyte differentiation during development. Whereas induced expression of Nkx2.2 in early oligodendrocyte precursor cells (OPCs) causes precocious differentiation of oligodendrocytes, conditional ablation of Nk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 37 publications
3
129
0
Order By: Relevance
“…This finding is not surprising considering that key factors such as NKX2.2, OLIG1/2 and SOX10, which have been shown to be crucial for NG2-glia differentiation, are still present and are not affected by the loss of ASCL1. In contrast, Olig1 Cre conditional knock-out of Pdgfrα resulted in a drastic decrease in the number of OPC/NG2-glia in the spinal cord (Zhu et al, 2014), a phenotype that is similar but more severe than the Olig1 Cre ;Ascl1 -CKO observed in this study (Fig. 8).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This finding is not surprising considering that key factors such as NKX2.2, OLIG1/2 and SOX10, which have been shown to be crucial for NG2-glia differentiation, are still present and are not affected by the loss of ASCL1. In contrast, Olig1 Cre conditional knock-out of Pdgfrα resulted in a drastic decrease in the number of OPC/NG2-glia in the spinal cord (Zhu et al, 2014), a phenotype that is similar but more severe than the Olig1 Cre ;Ascl1 -CKO observed in this study (Fig. 8).…”
Section: Discussionmentioning
confidence: 46%
“…The generation, development, and differentiation of NG2-glia in the CNS is a complex process across both space and time, and requires the precise regulation and function of multiple genes, particularly those encoding transcription factors ( Olig1/2, Nkx2.2, Ascl1, Sox10, Prox1, Smarca4/Brg1 , Myrf, and Sox17 ) (Hornig et al, 2013; Kato et al, 2015; Li, Lu, Smith, & Richardson, 2007; Lu et al, 2002; Stolt et al, 2004; Sugimori et al, 2007; Sugimori et al, 2008; Yu et al, 2013; Zhou, Choi, & Anderson, 2001; Zhou & Anderson, 2002; Zhu et al, 2014). Gain-of-function and loss-of-function studies in the last couple of decades have been informative in revealing the general mechanisms of how OLPs are specified by Sonic hedgehog (SHH) and the various transcription factors to give rise to NG2-glia and eventually myelinating OLs (Rowitch & Kriegstein, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm this, we examined the expression of this gene in Olig1 mutant and Nkx2.2 mutant spinal cords using TAPP1 ISH. It was previously shown that the differentiation of OLs is delayed and/or reduced in the spinal cords of these mutants [10,15] .…”
Section: Tapp1 Is Selectively Expressed In Differentiating Oligodendrmentioning
confidence: 94%
“…5 μm frozen sections were immunostained for Nkx2.2 (74.5A5, Developmental Studies Hybridoma Bank, University of Iowa, Iowa city, IA), or for anti-neural glial antigen-2 (NG2, AB5320, Millipore). Nkx2.2 is a homeodomain transcription factor expressed by OPCs that regulates differentiation (Cai et al 2010; Qi et al 2001; Zhu et al 2014). NG2 is a chondroitin sulfate proteoglycan that recognizes OPCs in the intact nervous system (Nishiyama et al 2009).…”
Section: Methodsmentioning
confidence: 99%